Comprehensive strategic management : a guide for students, insight for managers - Bolland, Eric J. (Emerald Publishing Limited, 2017)
A breakthrough approach to strategic management is presented in this book. Traditionally, strategic management texts have offered a largely conceptual presentation of the subject followed by a separate and dominant section containing many different types of case studies. This book breaks from that by having fewer case studies but they are attached to the chapters in which relevant material is presented. This reinforces the subject for student and manager alike. Additionally, important concepts from the academic treatment of strategic management and the practice of it in organizations are integrated by using findings and drawing implications from the leading strategic management journals and the writings from top business publications. Consequently, all readers will become familiar with the practical tools of strategy management, how to use these tools and solve real world strategy issues. This book also sorts through the myriad of strategy research and theory to highlight the intellectual pillars which support the subject.- Resumé vydavatel